Influencing factors on CPAP adherence and anatomic characteristics of upper airway in OSA subjects. Issue 51 (December 2017) - Park, Pona; Kim, Jinil; Song, Yoon Jae; Lim, Jae Hyun; Cho, Sung Woo; Won, Tae-Bin; Han, Doo Hee; Kim, Dong-Young; Rhee, Chae Seo; Kim, Hyun Jik
Abstract : Abstract: Although continuous positive airway pressure (CPAP) is the most effective treatment modality, poor adherence still remains a problem for obstructive sleep apnea (OSA) treatment and there is little evidence regarding how this might be improved. This study aims to analyze the anatomic and clinical factors of OSA subjects who failed to comply with CPAP therapy. The medical records of 47 OSA subjects who received CPAP therapy as a first-line treatment modality were retrospectively reviewed. The medical records were reviewed for demographic and polysomnographic data and anatomic findings of the nasal cavity and oropharynx. 24 patients who adhered to CPAP therapy and 23 patients who were nonadherent were enrolled in the study. There were no statistically significant differences in sleep parameters between CPAP-adherent patients and CPAP nonadherent subjects. Mean body mass index of CPAP nonadherent group was significantly higher than CPAP adherent group. Higher grades of septal deviation and hypertrophic change of the inferior turbinate were observed more in the CPAP nonadherent group. In addition, CPAP nonadherent subjects showed considerably bigger tonsils and higher grade palatal position comparing with the CPAP adherent subjects. Subjective discomfort including inconvenience, mouth dryness, and chest discomfort were the main problems for OSA subjects who did not comply with CPAP therapy. Excessive upper airway blockage in the nasal cavity and oropharynx was predominant in CPAP nonadherent subjects, which might cause the reported subjective discomfort that reduces CPAP compliance. Therefore, resolution of these issues is needed to enhance CPAP compliance for control of OSA.